Secure Data Sharing In Cloud Computing By Implementing Amednded Attribute Based Data Sharing Scheme (International Journal of Engineering and Computer Science, 2017)
Cloud computing, is a booming computing paradigm, allowing users to remotely hoard their data in a server and provide services on-demand. To ensure the data security in the cloud, Data access control is an efficient approach. the data access control turn out to be a challenging issue in cloud storage systems due to data outsourcing and despaired cloud service providers. Cipher text-Policy Attribute based Encryption (CP-ABE) is regarded as one of the most suitable technologies in cloud storage for data access control, since it gives data owners more undeviating control on access policies. However, it is complicated to directly employ existing CP-ABE schemes to data access control for cloud storage systems due to the attribute revocation issue. A data owner (DO) is generally willing to store huge amounts of data in cloud storage system for saving the cost on local data management. Without any of the data security mechanism, The cloud service provider (CSP), however, can completely gain access to all data of the user. Data owner is permitted to fully regulate the access policy correlated with the data which has to be disclosed. However, CP-ABE is limited to a potential security risk that is known as key escrow problem whereby the secret keys was issued by a trusted key authority to the users. In the proposed system, attribute-based data sharing scheme is revisited in order to solve the issue of “key escrow” and also to improve the persuasiveness of attribute, so that the resultant scheme is more gracious to the application that are implemented through cloud computing. An improved two-party key issuing protocol has been implemented that which assure that neither key authority nor cloud service provider can be conceded the whole secret key of a individual user.